Implementasi Budaya Komunikasi pada Proses Belajar Mengajar pada Kegiatan Pengabdian Masyarakat Desa Kutambelin - Abdurrahman Abdurrahman; Wiwit Fitriyani; Brilian Heaby; Endy Matalauta; Yusril Mahendra (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
This service activity aims to improve teaching methods or methods in teaching and learning processes and activities carried out by teachers to students in the existing communication culture. The implementation method consists of several stages, including: (1) observation, (2) planning, (3) preparation, (4) implementation and (5) evaluation. This study uses test test techniques and interviews with students, teachers and the community. This activity has a direct impact on the daily life of every community which can be implemented in the environment in the application of communication so that it coexists with the existing culture by continuously improving the quality or values ​​that exist in each existing community.